Postoperative outcomes of resectable periampullary cancer accompanied by obstructive jaundice with and without preoperative endoscopic biliary drainage - Pattarapuntakul, Tanawat; Charoenrit, Tummarong; Netinatsunton, Nisa; Yaowmaneerat, Thanapon; Pitakteerabundit, Thakerng; Ovartlarnporn, Bancha; Attasaranya, Siriboon; Wong, Thanawin; Chamroonkul, Naichaya; Sripongpun, Pimsiri (Frontiers in Oncology, 2022)
Background Preoperative biliary drainage (PBD) is useful in resectable periampullary cancer with obstructive jaundice. Whether it is better than direct surgery (DS) in terms of postoperative complications and mortality is controversial. Methods All cases of successful pancreaticoduodenectomy (PD) in patients with periampullary cancer with obstructive jaundice performed between January 2016 and January 2021 were retrospectively reviewed. Endoscopic PBD was performed; data pertaining to serum bilirubin level, procedural technique, and duration before surgery were obtained. The incidence of postoperative complications and survival rate were compared between the PBD and DS group. Results A total of 104 patients (PBD, n = 58; DS, n = 46) underwent curative PD. The mean age was 63.8 ± 10 years and 53 (51%) were male. Age, body mass index (BMI), sex, Eastern Cooperative Oncology Group status, presence of comorbid disease, initial laboratory results, and pathological diagnoses were not significantly different between the two groups. The incidence of postoperative complications was 58.6% in the PBD group while 73.9% in the DS group (relative risk [RR] 1.26, 95% confidence interval [CI] 0.92, 1.73, p=0.155) and the difference was not significant except in bile leakage (RR 8.83, 95% CI 1.26, 61.79, p = 0.021) and intraoperative bleeding (RR 3.97, 95% CI 0.88, 17.85, p = 0.049) which were higher in the DS group. The one-year survival rate was slightly less in the DS group but the difference was not statistically significant. The independent predictors for death within 1-year were intraoperative bleeding and preoperative total bilirubin > 14.6 mg/dL. Conclusions PBD in resectable malignant distal biliary obstruction showed no benefit in terms of 1-year survival over DS approach. But it demonstrated the benefit of lower risks of intraoperative bleeding, and bile leakage. Additionally, the level of pre-operative bilirubin level of over 14.6 mg/dL and having intraoperative bleeding were associated with a lower 1-year survival in such patients. Overall, PBD may be not necessary for all resectable periampullary cancer patients, but there might be a role in those with severely jaundice (>14.6 mg/dL), as it helps lower risk of intraoperative bleeding, and might lead to a better survival outcome.